Diverse and Dynamic Interactions: A Model of Suicidal Men's Help Seeking as It Relates to Health Services. Issue 1 (January 2018) - River, Jo
There is a striking gender difference in suicide rates worldwide, with men accounting for approximately 80% of all suicide deaths. In contradictory public discussions, suicidal men are presented sometimes as victims of "poor" health services and sometimes as irremediable, "poor" help seekers. A more substantive theory of suicidal men's help seeking, which moves beyond homogenizing accounts to examine the complex interplay between help seeking and health services, is now required. Eighteen life history interviews were undertaken with men who had engaged in nonfatal suicide. Interviews were analyzed within a theoretical framework of gender relations. The findings challenge static and uniform notions of suicidal men's help seeking. While a few men actively avoided health services, others actively sought help, and in many cases help-seeking practices were triggered by unsolicited encounters with health services. Responsibility for help-seeking behavior did not rest solely with suicidal men. Men's help-seeking practices could either be facilitated or blocked by the character of the professional support that was available. Men in this study overwhelmingly rejected services that framed emotional distress and suicidal behavior as mental illness.